Mini web server wires up intelligent buildings. - Greenhalgh, Tim (Times Higher Education Supplement, 1999)
Presents the world's smallest Web server built at the University of Massachusetts. Cost; Size; How it can be used in houses and buildings; Comments from developer H. Shrikumar.